Real Time Estimation of Loads in Radial and Unsymmetrical Three-Phase Distribution Networks - Dzafic,I; Gilles,M; Jabr,RA; Pal,BC; Henselmeyer,S (IEEE Transactions on Power Systems, 2013)
This paper presents a load estimator for large scale asymmetric distribution networks. It is based on iterating between 1) a weighted least squares (WLS) estimator that attempts to adjust the forecasted load group values to the telemetered measurements and 2) a three-phase load flow employing the Fortescue transformation. The WLS estimation phase explicitly handles Y- and $Delta$-connected unbalanced loads and area losses; it can also identify bad measurements based on the estimated load scaling factors. Numerical results show that the proposed load estimator is superior to conventional load allocation based on current balancing, and that its performance is commensurate with the requirements of real-time applications on unsymmetrical radial distribution networks having up to one million nodes.